PERANAN PEMBIMBING AGAMA ISLAM DALAM MEMBERIKAN MOTIVASI PENTINGNYA BELAJAR AL-QUR’AN DI MAJELIS TAKLIM BANDUNGAN KAMPUNG SAWAH LEGA KECAMATAN PASIRWANGI KABUPATEN GARUT - Muhammad Saepul Ulum (INSTITUT AGAMA ISLAM NEGERI METRO, 2020)
The focus of this research is the members of the Bandungan Taklim Assembly of Kampung Sawah Lega, Pasirwangi Subdistrict, Garut Regency, which notes the background of the farmers who have concerns about the importance of learning the Qur'an, which in their daily life every morning until evening takes care of their agricultural land in the mountains and rice fields. and in the evening gather with family members so that at an advanced age they want to try to get closer to the almighty Allah Almighty by studying reading the Qur'an in the Taklim Bandungan Assembly. This research was conducted at the Taklim Bandungan Assembly. The formulation of the problem in this study is how the Motivation of Belaja Al-Qur'an at the Taklim Bandungan assembly. And How the Role of Islam in Increasing Motivation the importance of Learning the Qur'an at the Taklim Bandungan Assembly. The research method used in this study is a qualitative research with descriptive design, a case study method with a phenomenological approach, the informants in this study consisted of 1 Islamic religious counselor and 4 members of the Bandungan Taklim Assembly Jama'ah who routinely attend recitals every week. The data collection techniques using the method of observation, in-depth interviews and documentation. The results achieved from this study indicate that the role of Islamic religious supervisors is very important in increasing the motivation of the importance of learning the Koran for the Jama'ah Taklim Bandungan Assembly, in the process of Islamic religious guidance beginning with the recitation of the Qur'an simultaneously which then proceed with the Koran independently with listened to and observed by supervisors and other worshipers, continued tausiyah and Question and Answer. The method of giving motivation is used by religious counselors, namely the one-way lecture method and the question and answer process.